Epigenetic Studies of Chinese Herbal Medicine: Pleiotropic Role of DNA Methylation - Guo, Wenqian; Ma, Han; Wang, Chong-Zhi; Wan, Jin-Yi; Yao, Haiqiang; Yuan, Chun-Su (Frontiers in Pharmacology, 2021)
Accumulating knowledge has been achieved on DNA methylation participating in numerous cellular processes and multiple human diseases; however, few studies have addressed the pleiotropic role of DNA methylation in Chinese herbal medicine (CHM). CHM has been used worldwide for the prevention and treatment of multiple diseases. Newly developed epigenetic techniques have brought great opportunities for the development of CHM. In this review, we summarized the DNA methylation studies in CHM, elucidated how DNA methylation participates in the processes of CHM botanical drugs growth and bioactive compound biosynthesis influenced by environmental factors, in pharmaceutical mechanisms of CHM formulae, CHM herbs, and herbal derived compounds, and in the constitution theory research and other essential issues of CHM. This newly developed field of DNA methylation is up-and-coming to address many complicated scientific questions of CHM; it thus not only promotes disease treatment but also facilitates health maintenance.